Politisasi Agama dalam Ranah Konflik di Indonesia (Sebuah Tinjauan Kritis) - Mahatva Yoga Adi Pradana; Marwa Parasmana; Hidayati Fajrin; Muhammad Fiqri Fadilah (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
Conflict in the Indonesian state cannot be separated from the influence of politics and religious understanding. The symbolization of religion and politics became part of the conflicts that were often faced. This influence is due to the existence of political forces that deliberately put religion as a tool of movement. Where religion, which is a transcendental form of human beings, becomes very political for the sake of economic interests. Muslim societies are trying to reform the society or the community in which the state survives. In addition, the elite sought to reform the country. This idea tries to interpret the Islamization of Java as an alternative conflict and accommodation between competing identities between Java and Islam. This paper uses a qualitative approach by strengthening literature reviews sourced from existing realities. The results found that the politicization of religion prioritizes its main political aspects and uses religion as a tool to create conflict. This happens because religion is one of the ways to create conflicts both vertically and horizontally. Therefore, in minimizing conflicts, Pancasila ideology is needed as a mediator and conflict resolution. Keywords: Conflict, Politicization of Religion, Religion, Politics